2017
DOI: 10.15406/ogij.2017.06.00215
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Pattern in Preterm Prelabour Rupture of the Fetal Membranes in South-Western Nigeria

Abstract: Background: Preterm prelabour rupture of the fetal membranes (PPROM) complicates 3% to 4% of all pregnancies. It is responsible for 40% of all preterm births with its attendant high perinatal morbidity and mortality.Objective: The aim of this study was to determine the prevalence of PPROM; with profile and antibiotic susceptibility of isolated organisms.Methodology: It was a prospective study carried out between 10th July 2011 and 22nd August 2012 among recruited pregnant women that met the inclusion criteria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…A significant difference in the positive culture rates was found in the two comparison groups, which suggests a strong correlation between the infection of the genital tract and the occurrence of PPROM. A similar association was found in the study done by Adewumi et al 2 This study has reported E. coli to be the commonest organism isolated in 52.6% of the PPROM cases. It was also found to be the commonest organism in the reported literature contributing to 30-53% in the studies done over the past few years.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A significant difference in the positive culture rates was found in the two comparison groups, which suggests a strong correlation between the infection of the genital tract and the occurrence of PPROM. A similar association was found in the study done by Adewumi et al 2 This study has reported E. coli to be the commonest organism isolated in 52.6% of the PPROM cases. It was also found to be the commonest organism in the reported literature contributing to 30-53% in the studies done over the past few years.…”
Section: Discussionsupporting
confidence: 89%
“…The positive culture rates in PPROM range from 21% and 45% according to the studies conducted by Shivaraju et al, 6 Adewumi et al, 2 Shilpa et al, 7 and Devi. 8 The findings obtained in this study also fall in this particular range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…addition, there are risks associated with chorioamnionitis and placental abruption. 2 Group B Streptococcus (GBS) is the main pathogen which has been observed in lots of western maternal genital tract in PPROM cases. But some studies in other countries have demonstrated completely different results which showed the presence of other microorganisms as the main pathogens of PPROM.…”
mentioning
confidence: 99%